Cloning and characterization of the low-affinity cyclic AMP phosphodiesterase gene of Saccharomyces cerevisiae. - Nikawa, J (1987)
Saccharomyces cerevisiae contains two genes which encode cyclic AMP (cAMP) phosphodiesterase. We previously isolated and characterized PDE2, which encodes a high-affinity cAMP phosphodiesterase. We have now isolated the PDE1 gene of S. cerevisiae, which encodes a low-affinity cAMP phosphodiesterase. These two genes represent highly divergent branches in the evolution of phosphodiesterases. High-copy-number plasmids containing either PDE1 or PDE2 can reverse the growth arrest defects of yeast cells carrying the RAS2(Val-19) mutation. PDE1 and PDE2 appear to account for the aggregate cAMP phosphodiesterase activity of S. cerevisiae. Disruption of both PDE genes results in a phenotype which resembles that induced by the RAS2(Val-19) mutation. pde1- pde2- ras1- ras2- cells are viable.